PENGARUH UKURAN KANTOR AKUNTAN PUBLIK (KAP) DAN HIRARKI JABATAN TERHADAP PROFESIONALISME AUDITOR PADA KANTOR AKUNTAN PUBLIK (KAP) DI WILAYAH JAKARTA SELATAN - Hj. Dewi Rejeki, SE., Ak., M.Ak.; Agnes Vanesa (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
This study was conducted to determine the effect of partially or simultaneously between the size of Public Accounting Firms (KAP) and hierarchical positions on the professionalism of auditors in Public Accounting Firms (KAP) at South Jakarta. This research is done in the Public Accounting Firms (KAP) at South Jakarta. The methods used for data collection is through a survey of primary data. The analytical method used is a method of quantitative and qualitative approaches. The results of the study showed that simultaneous size of Public Accounting Firms (KAP) and the hierarchical positions of powerful positions significantly and positively on the professionalism of auditors and the results of the partial indicates that the variable size of Public Accounting Firms (KAP) and the hierarchical positions on the professionalism of auditors in Public Accounting Firms (KAP) at South Jakarta, where the second factor it will contribute to the professionalism of auditors as big as 89,6%. The conclusions of this study, the variable size of Public Accounting Firms (KAP) and hierarchical positions of powerful positions significantly and positively to the professionalism of auditors variables either partially of simultaneously. The suggestion from this study, expected variables need to be improved such as gender, experience, independence, audit situations, ethics, knowledge, ethical perception, and role conflict.